Implications of Artificial Intelligence (AI) on structural transformation and social control dynamics of society - Zaini, Ahmad; Harahap, Faisal Sadat Soaduon; Setha, Donny; Na’im, Khairun (Journal of Law Science, 2025)
The development of Artificial Intelligence (AI) has significantly impacted structural transformation and the dynamics of social control within society. AI not only changes how individuals interact with the world but also influences various sectors such as the economy, education, and government. Large-scale automation and data processing enable greater efficiency but also present complex social challenges, including technological access inequality, job displacement, and ethical and privacy concerns. This study aimed to analyze the implications of artificial intelligence (AI) on the structural transformation and dynamics of social control in society. This article discusses how AI has become a catalyst for social change, affecting human interaction patterns, job structures, and the legal regulations needed to ensure that technological advancements align with principles of justice and inclusivity. A normative juridical approach is used to analyse the impact of AI on legal and social norms, as well as how regulations can address emerging challenges. The study’s findings indicate that AI holds significant potential to improve human quality of life through efficiency and innovation but may also pose threats if not accompanied by appropriate regulations. Therefore, balanced policies are required to ensure that technological advancements are utilized while protecting human rights, allowing AI to contribute positively to social transformation. This study highlights the need for balanced and ethical regulation of AI. Practically, the findings help policymakers design fair rules to minimize the risks and maximize the benefits of AI for society